Pandangan Proses Transaksi PayLater Terhadap Perilaku Konsumtif Dalam Prespektif Ekonomi Syariah - Priska Cintya; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Digital transformation has shaped a more connected ecosystem and opened up new opportunities, particularly in the financial sector. One significant innovation is the Paylater payment service, which allows consumers to buy goods or services now and pay later. This service offers great convenience and flexibility, making it popular among consumers, especially millennials. The use of PayLater services in consumer transactions has become an increasingly relevant topic in the context of Islamic economics. However, the popularity of Paylater raises concerns from an Islamic economic perspective that emphasizes fairness, transparency, and usury-free. This research aims to provide a deeper understanding of how PayLater transactions are viewed within the framework of Islamic economics and how responsible financial management can be carried out in accordance with sharia principles. The research method used is descriptive with a qualitative approach carried out by deeply processing the results obtained from various literature sources. The results show that the use of PayLater services in consumer transactions is contrary to sharia law besides that it also causes excessive consumptive behavior, and the impact of uncontrolled debt accumulation which is prohibited in sharia law.